Anti-parasitic drug discovery against Babesia microti by natural compounds: an extensive computational drug design approach - Akash, Shopnil; Hosen, Md. Eram; Mahmood, Sajjat; Supti, Sumaiya Jahan; Kumer, Ajoy; Sultana, Shamima; Jannat, Sultana; Bayıl, Imren; Nafidi, Hiba-Allah; Jardan, Yousef A. Bin; Mekonnen, Amare Bitew; Bourhia, Mohammed (Frontiers in Cellular and Infection Microbiology, 2023)
Tick-borne Babesiosis is a parasitic infection caused by Babesia microti that can infect both animals and humans and may spread by tick, blood transfusions, and organ transplantation. The current therapeutic options for B. microti are limited, and drug resistance is a concern. This study proposes using computational drug design approaches to find and design an effective drug against B. microti.The study investigated the potentiality of nine natural compounds against the pathogenic human B. microti parasite and identified Vasicinone and Evodiamine as the most promising drugs. The ligand structures were optimized using density functional theory, molecular docking, molecular dynamics simulations, quantum mechanics such as HOMO-LUMO, drug-likeness and theoretical absorption, distribution, metabolism, excretion, and toxicity (ADMET), and pharmacokinetics characteristics performed. The results showed that Vasicinone ( -8.6 Kcal/mol and -7.8 Kcal/mol) and Evodiamine (-8.7 Kcal/mol and -8.5 Kcal/mol) had the highest binding energy and anti-parasitic activity against B. microti lactate dehydrogenase and Babesia microti lactate dehydrogenase apo form. Once, and the strongest binding energy was reported by Vasicinone and Evodiamine, the compounds were evaluated through molecular dynamics simulation at 100ns and determined their stability when they form complexes with the targeted receptors. Finally, the pkCSM web server is employed to predict the ADMET qualities of specific molecules, which can help prevent negative effects that arise from taking the treatment. The SwissADME web server is used to assess the Lipinski rule of five and druglikeness properties including topological polar surface area and bioavailability. The Lipinski rule is used to estimate significant drug-like. The theoretical pharmacokinetics analysis and drug-likeness of the selected compounds are confirmed to be accepted by the Lipinski rule and have better ADMET features. So, to confirm their experimental value, these mentioned molecules should be suggested to carry out in wet lab, pre-clinical and clinical levels.